Dracula - Stoker, Bram. (London : Penguin Books, 2003)
The volume includes an introduction by Roger Luckhurst that considers the Gothic genre and vampire legend, discusses the vampire tale as sexual allegory, and outlines the social and cultural contexts that feed into the novel, including the New Woman, new technology, race, immigration, and religion. In addition, Luckhurst provides comprehensive explanatory notes that flesh out vampire mythology and historical allusions, plus an appendix featuring Stoker's short story, "Dracula's Guest," an early draft or abandoned chapter that was not published as part of the novel. --from publisher description.
Keywords: Vampires -- Fiction; FICTION -- General